A 3-D Meshless Method for Solving Maxwell's Equations by Using the Steger-Warming Flux Vector Splitting Approach. (September 2020) - Gao, Yukun; Chen, Hongquan; Xu, Shengguan; Zhang, Jiale; Cao, Cheng; Gao, Huanqin
Abstract: In order to solve Maxwell's equations so as to study the electromagnetic stealth characteristics of targets, a 3-D meshless method is developed. According to the meshless method, the spatial derivatives on clouds of points are computed by using the weighted least square approach. After that, the Steger-Warming flux vector splitting approach is used to calculate the physical flux of Maxwell's equations. By using the developed method, the calculated bistatic radar cross sections (RCS) of a 3-D sphere are obtained, which are agree with the series solutions. Finally, the electromagnetic scattering characteristics for a 3-D stealth aircraft model with different situations is given, which shows the developed method has the ability to accommodate complicated 3-D configurations with multi-element.